Cryosurgery combined with topical interventions for actinic keratosis: a systematic review and meta‐analysis. (1st April 2019) - Heppt, M.V.; Steeb, T.; Ruzicka, T.; Berking, C.
Summary: Background: Actinic keratoses (AKs) are early in situ carcinomas of the skin caused by cumulative sun exposure. Cryosurgery is an easy and practicable lesion‐directed approach for treatment of isolated lesions. Objectives: To investigate whether an upfront combination of cryosurgery with a topical intervention is superior to cryosurgery alone for treatment of AK. Methods: We performed a systematic literature search in MEDLINE, Embase and CENTRAL and hand searched pertinent trial registers for eligible randomized controlled trials until 17 July 2018. Results from individual studies were pooled using a random effects model. The risk of bias was estimated with the Cochrane Risk of Bias Tool and the quality of evidence of the outcomes with the GRADE approach. Results: Out of 1758 records initially identified, nine studies with a total sample size of 1644 patients were included. Cryosurgery in combination with a topical approach showed significantly higher participant complete clearance rates than monotherapy [risk ratio (RR) 1·74, 95% confidence interval (CI) 1·25–2·43, I 2 = 73%, eight studies]. The participant partial clearance rate was not statistically different (RR 1·64, 95% CI 0·88–3·03, I 2 = 77%, three studies). The number of patients who completed the study protocol and did not withdraw due to adverse events was equal in both groups (RR 0·98, 95% CI 0·95–1·01, I 2 = 75%, seven studies). The studies were estimated to have high risk for selective reporting bias. Conclusions: Our results suggest the superiority of a combination regimen for AK clearance, with equal tolerability. This study highlights the importance of a field‐directed approach in patients with multiple AKs or field cancerization.